2015
DOI: 10.1074/jbc.m114.596866
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Long Noncoding RNA MALAT1 by miR-101 and miR-217 Inhibits Proliferation, Migration, and Invasion of Esophageal Squamous Cell Carcinoma Cells

Abstract: Background: MALAT1, a highly conserved long non-coding RNA (lncRNA), acts as oncogene in multiple human cancers. Results: miR-101 and miR-217 can silence MALAT1 expression and then inhibit esophageal cancer proliferation, migration and invasion. Conclusion: Tumor suppressor miR-101 and miR-217 can negatively regulate MALAT1 expression. Significance: These data provide a new mechanism for MALAT1 regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
220
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(229 citation statements)
references
References 44 publications
(39 reference statements)
9
220
0
Order By: Relevance
“…Our results indicated that the direct binding ability of the miR-101b on the MALALT1 transcript, in line with the previous report. 27 Additionally, we identified Rac1 as a new target of miR-101b in liver fibrosis, which amplifies the repertoire of miR-101b targets. Several studies have reported that Rac1 signaling is involved in the pathogenesis of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results indicated that the direct binding ability of the miR-101b on the MALALT1 transcript, in line with the previous report. 27 Additionally, we identified Rac1 as a new target of miR-101b in liver fibrosis, which amplifies the repertoire of miR-101b targets. Several studies have reported that Rac1 signaling is involved in the pathogenesis of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miR-101b is downregulated in liver fibrosis, 7 which was confirmed by our data. Wang et al 27 demonstrated that miR-101 can inhibit MALAT1 expression in esophageal squamous cell carcinoma. However, whether MALAT1 can regulate miR-101 expression has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevation of MALAT1 is achieved through the following: (1) transcriptional activation on the epigenetic level such as demethylation of histone H3K9 28 or on the genetic level such as through transforming growth factor-β (TGF-β), 29 cyclic AMPresponsive element binding (CREB), 30 Wnt/β-catenin pathway, 31 or SOX17; 32 (2) post-transcriptional regulation, such as miRNA-mediated silencing, as demonstrated by miR-125, 33 miR-9, 34 miR-101, and miR-217. 35 In addition to functioning as a marker for malignancy, MALAT1 upregulation significantly correlates with the poor prognosis of cancer patients, rendering this molecule a prognostic indicator. [36][37][38] In this study, we found that MALAT1 and miR-204 mutually and negatively regulated the expression of each other, and their levels negatively correlated with each other in HCC tissues, suggesting that although miR-204 could control the expression of MALAT1, the upregulation of MALAT1 in HCC tissues would downregulate the level of miR-204, which in turn further elevates MALAT1 and exacerbates the phenotypes induced by MALAT1.…”
Section: Discussionmentioning
confidence: 99%
“…In oesophageal squamous cell carcinoma, silencing the MALAT1 expression resulted in the inhabitation of proliferation, migration, and invasion [57,58]. Other studies also reported the deregulation of MALAT1 in bladder cancer and renal cancers [59,60].…”
Section: Metastasis-associated Lung Adenocarcinoma Transcript 1 (Malat1)mentioning
confidence: 91%